Apple Scab (Venturia inaequalis Wint) Management Using a Novel Fungicide Combination in the North-Western Himalayas of India - Verma, Shalini; Gautam, H. R.; Khosla, Kishore (International Journal of Economic Plants, 2022)
Apple (Malus×domestica) is commercially most important horticultural crop grown in the north-western Himalayan region of India. The apple scab caused by fungi Venturia inaequalis (Cooke) Wint., is a devastating disease of apple aided by cool, moist climate during early spring. The present study on evaluation of effective fungicides against apple scab was undertaken in Himachal Pradesh during the years 2016 and 2017 under natural epiphytotic conditions. The application of carbendazim 25%+flusilazole 12.5% SE (0.08%) significantly decreased the apple scab disease in the present study. This resulted in maximum reduction of per cent conidia and conidial germination of V. inaequalis at the concentrations tested. It was superior and effective in comparison to other fungicides. Since the new combination of carbendazim 25% + flusilazole 12.5% SE exhibits systemic activity and both the fungicides have different modes of action, therefore, such a new combination can delay or prevent the build-up of resistance in the pathogen and can be effectively utilized as a promising fungicide for the control of apple scab disease.